Validation of a photographic method of measuring corneal diameter. Issue 7 (July 1989) - Robinson, J; Gilmore, K J; Fielder, A R
Abstract : A photographic method for measuring corneal diameter using the Medical-Nikkor f200 mm lens is described. Measurements were compared with those obtained by calipers (46 eyes of 25 patients) and by placing a ruler either near the eye (123 eyes of 64 patients) or on the nose (98 eyes of 55 patients). Over all we found good correlation between photographic and caliper measurements (r = 0.94). No significant correlation was found between photographic measurements and estimates made with the ruler either near the eye or on the nose (r = 0.65 and 0.31 respectively). Modifications to our system are suggested which may provide an accurate, simple, non-invasive method of measuring corneal diameter in ophthalmic clinics.